Ductile fracture modelling and J-Q fracture mechanics: a constraint based fracture assessment approach - N.O. Larrosa; R.A. Ainsworth (Fracture and Structural Integrity)
The reduced state of stress triaxiality observed in shallow cracked components allows an increased capacity to resist crack propagation compared to that observed in deeply cracked specimens. This may be regarded as a higher fracture toughness value which allows a reduction in the inherent conservatism when assessing components in low constraint conditions. This study uses a two-parameter fracture mechanics approach (JQ) to quantify the level of constraint in a component (e.g. a pipe with a surface crack) and in fracture test specimens, i.e. single edge tension [SE(T]) and compact tension [C(T)] specimens, of varying constraint level. The level of constraint of the component is matched to a specific test specimen and therefore the ability of the structure to resist fracture is given by the fracture toughness of the test specimen with a similar J-Q response. Fracture toughness values for different specimens have been obtained from tearing resistance curves (J-R curves) constructed by means of a virtual testing framework. The proposed engineering approach shows that the combination of a local approach and two-parameter fracture mechanics can be used as a platform to perform more accurate fracture assessments of defects in structures with reduced constraint conditions